Crime Control in the 2008 Presidential Election: Symbolic Politics or Tangible Policies? - Marion, Nancy E. (American journal of criminal justice, 2012)
Presidential candidates regularly use crime issues to help win electoral support. Contrary to conventional wisdom, crime control became an issue in the 2008 presidential campaign. Despite decreasing crime rates and public opinion focused only temporarily on illegal immigration, the three major presidential candidates (Obama, Clinton, & McCain) discussed many anticrime initiatives during the campaign. Unlike past research which has found presidential candidates use primarily symbolic rhetoric in their anticrime rhetoric, all three presidential candidates in the 2008 presidential election were found to have employed tangible statements. The article discusses the different findings, making recommendations for future research.